Excerpta medica. Section 47: Virology.
Monthly. Abstracts from world literature about all aspects of virology and virus research. Classified arrangement of entries. Subject, author indexes. References in this section were formerly carried in Excerpta medica. Section 4, Microbiology. About 4500 abstracts, 1971.